Beyond market and ierarchy : patriotic capitalism and the Jiuda Salt Refinery, 1914-1953 - Bun, Kwan Man.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Based on extensive archival research, Beyond Market and Hierarchy reconstructs how Fan waged modern China's war of salts. Led by his Jiuda Salt Industries, the nascent refined salt industry battled revenue farmers who, as a group, monopolized the production and distribution of evaporated salt.
Keywords: Industries; Trade; Business; Commerce; Microeconomics; Industrial organization; Economic history; Regional economics; Spatial economics